2017
DOI: 10.5433/1679-0359.2017v38n4p2019
|View full text |Cite
|
Sign up to set email alerts
|

Regional composition of carcass and tissue composition of cuts from lambs slaughtered with different subcutaneous fat thicknesses

Abstract: The aim of this study was to evaluate the influence of the subcutaneous fat thickness (SFT) on the regional composition of the carcass, the tissue composition of cuts, and the leg muscularity index of Santa Inês lambs. This experiment involved 24 uncastrated male lambs at approximately 100 days of age and at an average live weight of 22.70 ± 3.75 kg that were kept in the feedlot, where they received a complete pelleted diet formulated to provide a daily gain of 0.30 kg. The animals were slaughtered as they rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…This greater fat deposition slows the thickening of these cuts. The later growth of these cuts is explained because of their anatomical location whereby a greater fat accumulation is observed in the abdominal region (Andrade et al, 2017). Therefore, the relatively greater amounts of fat trim and mesenteric plus omental fat in CS-fed animals might be because these sheep were fed the diet that was highest in energy (Maciel et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This greater fat deposition slows the thickening of these cuts. The later growth of these cuts is explained because of their anatomical location whereby a greater fat accumulation is observed in the abdominal region (Andrade et al, 2017). Therefore, the relatively greater amounts of fat trim and mesenteric plus omental fat in CS-fed animals might be because these sheep were fed the diet that was highest in energy (Maciel et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, subcutaneous fat deposition (average of 2.97 mm) did not differ in lambs fed different dietary treatments. Previous research (Andrade et al, 2017) has shown that fat thickness around 3 mm provides better protection against moisture loss during carcass chilling when compared to 2 mm. The percentage of weight loss by cooling depends on factors such as pH, loss of moisture and chemical reactions that occur in the muscle.…”
Section: Fatty Acid Profile Levels Of Replacementmentioning
confidence: 96%
“…Alguns trabalhos elucidam o peso corporal de abate ideal, Grandis et al (2016) em ovinos Santa Inês encontra-se entre 15 e 35 kg, pois acima deste peso ocorre deposição acentuada de gordura, já Andrade et al (2017) para mesma raça recomendaram aos 33 kg.…”
Section: Introductionunclassified
“…espessura de gordura subcutânea foi utilizada como critério de abate em cordeiros porAndrade et al (2017) e fazendo um paralelo desta característica com o peso corporal de abate, encontraram que com aumento da espessura de gordura subcutânea ocorreu alteração na composição regional da carcaça e tecidual dos cortes, bem como a musculosidade da perna.Outro ponto importante, a ressaltar é que no Brasil a carcaça ovina é tradicionalmente separada em quatro cortes comerciais -pescoço, paleta, pernil e costilhar. No entanto, o costilhar pode sofrer novas divisões e, obter-se as costelas fixas (short rack ou carré curto), costelas flutuantes (french rack ou carré francês), baixo (peito) e o lombo com vazio (lombo com fraldinha).…”
unclassified